VISUAL RESEARCH METHODS IN CONTEMPORARY HUMANITARIAN KNOWLEDGE - A. I. Lojko; E. B. Yakimovich (Наука и техника)
The paper considers usage of visual methods in the field of anthropology, social philosophy and semiotics for investigating problems of identity, social habits and media cultural forms on the basis of  photographic practices.